Implementation of the Family Hope Program Policy in Bojong Village, Bungbulang District, Garut Regency (Study of the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018) - Nurhadi; Mulyanengsih; Aceng Ulumudin (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
The Family Hope Program (PKH) is a social protection program that provides cash assistance to poor families registered as Beneficiary Families (KPM), with a focus on improving the quality of human resources through education, health, and social welfare. This study aims to determine the implementation of the PKH policy in Bojong Village, identify inhibiting factors, and efforts to overcome them. The method used is qualitative with purposive sampling techniques, and data collection through observation, interviews, and documentation. The results of the study indicate that the implementation of PKH in Bojong Village was carried out through several stages, namely initial meetings, data input into the management information system, disbursement of funds, and verification of commitments. Although the implementation is not yet perfect, the community admits that this program is beneficial and eases their economic burden. The obstacles faced include technical and administrative obstacles, but are overcome through coordination between implementers and assistance to beneficiaries.